DO COMBINATION LEARNING MODELS CHANGE THE STUDY EFFECT SIZE? A META-ANALYSIS OF CONTEXTUAL TEACHING AND LEARNING - Maximus Tamur; Kanisius Mandur; Jerito Pareira (Journal Of Educational Experts (JEE), 2021)
Evidence-based research on the effects of Contextual Teaching-Learning (CTL) on mathematical abilities has been conducted. However, whether different combinations of learning can change the studies' effect size has not been explored. In order to fill this gap, it is necessary to conduct a meta-analysis study that can summarize the evidence on the effects of CTL and analyze how differences in learning combinations are related to the effect size (ES) of the study. The research sample is an individual study of the effects of CTL on various mathematical abilities identified from the ERIC database, the Scopus database, and Google Scholar. Based on the eligibility requirements, 26 studies were included in the analysis. The estimation method uses the random-effect model, and the Comprehensive Meta-Analysis (CMA) is used as a data processing tool. The analysis results showed that the ES of the study was 0.88. This show indicates overall, the use of CTL has a major significant on students' mathematical abilities. The results of further analysis explained that differences in the combination of learning moderated the implementation of CTL. These findings provide information to teachers and other related parties that CTL, combined with other methods, needs to be developed